Robert Ashdown Photography. - Ashdown, Robert (Toowoomba, [Queensland] : Robert Ashdown, 2009)
"I'm a naturalist and photographer living in Toowoomba, Australia. In this 'blog' I share some photographs, and often the stories behind them, as well as images and writing from various guests."
Title from title screen (viewed on 19 March 2014)
Mode of access: Available online. Address as at 11/04/2014
Selected for archiving
Keywords: Blogs -- Australia; Nature photography -- Australia; Australian